Dosagem do gene opaco-2 e teores de proteína e lisina no endosperma de sementes de milho (2ea mays L.) - Saraiva, Luiz Sérgio; de Almeida Filho, José (Revista Ceres, 2025)
Dosage effects of opaque-2 gene on the endosperm and percent of protein, lysine,and the ratio of lysine to protein, in seven inbred lines of corn, was studied.